INDUCTION OF CHLAMYDOSPORE IN FUSARIUM MONILIFORME - S. CHAUDHURI, D. N. MANDAL AND (Indian Phytopathology, 2002)
Fusarium moniliforme Sheld. produced chlamydospores under starved conditions and in large numbers in basic salt solution. In this medium, different factors like pH, quality of light, temperature, OzÂ·COz concentration, age of culture and spore concentration affected its induction. Chlamydospores were produced under low carbon concentration whereas nitrogen did not have any significant effect. Different sources of carbon and nitrogen also showed varied effect. Certain soil bacteria and one actinomycete species isolated from the rhizosphere of the host stimulated the production of chlamydospore.